STRATEGI GURU SDN 1 CIMAHPAR DALAM MENCIPTAKAN SUASANA BELAJAR YANG KONDUSIF BAGI GENERASI ALPHA DI ERA DIGITAL - Siti Aminah; Asep Sahrul Gunawan (STKIP Subang, 2026)
The development of digital technology has brought significant changes in the world of education, especially in dealing with the character of the alpha generation of students who have been familiar with technology in the digital era since an early age and have become accustomed to using technology. This generation has a tendency to prefer visual, interactive, and digital-based learning but also has a relatively short attention span. This study aims to analyze the strategies of teachers at SDN 1 Cimahpar in creating a conducive learning atmosphere for the alpha generation in the digital era. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through classroom observations, in-depth interviews involving teachers and students of SDN 1 Cimahpar as research subjects. The results show that teachers' strategies in creating a conducive learning atmosphere include the use of digital technology in learning, needing to implement interactive learning strategies, individual approaches to students at SDN 1 Cimahpar, and the creation of a positive and enjoyable learning environment. In addition, teachers also play a role as facilitators and motivators in supporting active student involvement during the learning process. However, there are challenges such as distractions from gadget use and low student concentration. Therefore, teachers are required to increase creativity and competence in managing learning in the classroom. By using appropriate strategies, a more conducive learning environment can be created, thus supporting the success of the learning process in the digital era. This research is expected to contribute to the development of more innovative learning strategies and serve as a reference for teachers in navigating the ever-evolving dynamics of education alongside the rapid advancement of digital technology.